Cardiac magnetic resonance in tropical endomyocardial fibrosis - Sharma, Ajay Kumar; Kumar, Tarun; Ramakrishnan, S. (International Journal of Research in Medical Sciences, 2019)
Background: Endomyocardial fibrosis has varied presentatation and difficult to diagnose. Aim to elucidate the role of Cardiac Magnetic Resonance (CMR) imaging in the evaluation of Endomyocardial Fibrosis (EMF) and to devise diagnostic criteria for the disease. Methods: Retrospective analysis of cases of restrictive cardiomyopathy referred for Magnetic resonance imaging over a period of 5 years. All patients underwent 1.5 T CMR imaging (Magnetom Avanto, Siemens, Germany) with standard cardiomyopathy protocol. Criteria for diagnosis of RCM included normal sized ventricles, normal/reduced systolic function, uni-/bi-atrial enlargement, normal pericardium and absent septal bounce. Cases diagnosed as EMF on CMR were included in this study. Statistical analysis performed using SPSS software. Results: EMF was diagnosed in 20 patients (31%) [12 males; age 39±18 years]. Ten patients had Right Centricular (RV) EMF, 3 had Left Ventricular (LV) EMF, while 7 had bi-ventricular EMF. Oedema indicating ongoing inflammation was seen in 4 (20%) cases. Apical thrombus was seen in 8(40%) cases and was present in 35% cases of RV and 20% cases of LV involvement. Subendocardial delayed enhancement was always present in the involved ventricle. The RV apex was obliterated in 100% of patients with RV EMF, while LV apex was similarly obliterated in 66% cases with LV disease. Mild-moderate pericardial effusion was observed in 8 patients. On the basis of CMR findings, the disease was classified as early necrotic phase in 1, thrombotic necrotic in 4 and late fibrotic phase in 13 and of different stages in ventricles in 2 cases. Conclusions: EMF was the commonest cause of RCM in this series. Major diagnostic criteria of EMF on CMR include subendocardial delayed enhancement and apical obliteration. Oedema and thrombus are variable findings, depending on disease severity.